Waist-to-Hip Ratio is Related to Body Fat Content and Distribution Regardless of the Waist Circumference Measurement Protocol, in Non-Alcoholic Fatty Liver Disease Patients - Pimenta, Nuno (2018)
Central accumulation and distribution of body fat (BF) is an important cardiometabolic risk factor. Waist-to-hip ratio (WHR), commonly elevated in non-alcoholic fatty liver disease (NAFLD) patients, has been endorsed as a risk related marker of central BF content and distribution, but no standardized waist circumference measurement protocol (WCmp) has been proposed. We aimed to investigate whether using different WCmp affects the strength of association between WHR and BF content and distribution in NAFLD patients. BF was assessed with Dual Energy X-ray Absorptiometry (DXA) in 28 NAFLD patients (19 males, 51 ± 13 yrs, and 9 females, 47 ± 13 yrs). Waist circumference (WC) was measured using four different WCmp (WC1: minimal waist; WC2: iliac crest; WC3: mid-distance between iliac crest and lowest rib; WC4: at the umbilicus) and WHR was calculated accordingly (WHR1, WHR2, WHR3 and WHR4, respectively). High WHR was found in up to 84.6% of subjects, depending on the WHR considered. With the exception of WHR1, all WHR correlated well with abdominal BF (r=0.47 for WHR1; r=0.59 for WHR2 and WHR3; r=0.58 for WHR4) and BF distribution (r=0.45 for WHR1; r=0.56 for WHR2 and WHR3; r=0.51 for WHR4), controlling for age, sex and body mass index (BMI). WHR2 and WHR3 diagnosed exactly the same prevalence of high WHR (76.9%). The present study confirms the strong relation between WHR and central BF, regardless of WCmp used, in NAFLD patients. WHR2 and WHR3 seemed preferable for use in clinical practice, interchangeably, for the diagnosis of high WHR in NAFLD patients.